2019
DOI: 10.1111/jphd.12307
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of public health genomics and applications to public health dentistry

Abstract: National and state public health genomics efforts exist to effectively and responsibly translate genome‐based knowledge to improve population health and reduce health disparities. Over the past two decades, public health genomics efforts have utilized the core public health functions of assessment, policy development, and assurance. Current evidence for a small number of genomic applications suggests that many lives could be saved if these were implemented in recommended populations. With the drastic increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The analysis of genomics testing and ocular disorders shows that participants possessed very limited prior knowledge about genomics and its potential benefits in ocular sciences. Although more recent studies have expanded the discussions on the relevance of genomics science [ 14 , 16 , 18 ], little attention has been paid to how genomics could be of help in the prevention or treatment of ocular diseases. Participants in this study, having been told of the potential nexus between genomics and ocular disease, subsequently showed a keen interest in genomics and expressed their willingness to participate in genomics research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of genomics testing and ocular disorders shows that participants possessed very limited prior knowledge about genomics and its potential benefits in ocular sciences. Although more recent studies have expanded the discussions on the relevance of genomics science [ 14 , 16 , 18 ], little attention has been paid to how genomics could be of help in the prevention or treatment of ocular diseases. Participants in this study, having been told of the potential nexus between genomics and ocular disease, subsequently showed a keen interest in genomics and expressed their willingness to participate in genomics research.…”
Section: Resultsmentioning
confidence: 99%
“…The positive contributions of genomics have been explored in various fields. For example, Duquette [ 14 ] observed that genomics would be relevant to public health dentistry. Also, in cancer research, genomics remains the major tool for understanding mutations that predispose individuals to the disease.…”
Section: Introductionmentioning
confidence: 99%